Outcomes of adults with repaired tetralogy of Fallot from the national Scottish Cohort. (24th August 2021) - Dobson, Richard J.; Ramparsad, Nitish; Walker, Niki L.; McConnachie, Alex; Danton, Mark H. D.
Abstract: Background: The adult population of repaired tetralogy of Fallot is increasing and at risk of pre-mature death and arrhythmia. This study evaluates risk factors for adverse outcome and the effect of pulmonary valve replacement within a national cohort. Methods: A retrospective cohort study of 341 adult repaired tetralogy of Fallot (16–72 years) managed through a single national service was undertaken incorporating over 1200 patient-years of follow-up. Demographics, cardiopulmonary exercise testing, cardiac magnetic resonance, reintervention (including pulmonary valve replacement), and clinical events were analysed. The influence of these parameters on a primary outcome (death or arrhythmia) was evaluated. Results: Compared with an age-/gender-matched population, patients experienced a reduced survival, particularly males over 55 years (standardised mortality ratio : 6.12, 95% CI: 1.64–15.66, p = 0.004). Cox proportional hazards modelling identified increased indexed right ventricle (RV) end-diastolic volume (hazard ratio (HR): 2.86, 95% CI: 1.4–5.85, p = 0.004) and female gender (HR (male): 0.37, 95% CI: 0.14–0.98, p = 0.045) to be predictors significantly associated with the primary outcome. Pulmonary valve replacement undertaken at indexed RV end-diastolic volume = 145 ml/m 2 reduced RV volumes and QRS duration but did not improve cardiopulmonary exercise testing nor NYHA class. Pulmonary valve replacement during cohort period was associated with increased risk of primary outcome (HR: 2.82, 95% CI: 1.36–5.86, p = 0.005). Conclusions: Although the majority of adult tetralogy of Fallot were asymptomatic in NYHA 1, cardiopulmonary exercise testing revealed important deficits. Tetralogy of Fallot survival was reduced compared to the general population. Female gender and increasing RV end-diastolic volume predicted adverse events. Pulmonary valve replacement reduced RV volumes and QRS duration but did not improve primary outcome.